Learning tools interoperability for enhancing a distributed personal learning environment with support for programming assignments - Jurado, Francisco; Redondo, Miguel A. (2014 International Symposium on Computers in Education (SIIE), 2014)
When using eLearning systems, there is not one unique tool that covers the entire learning/teaching process. In fact, an ideal scenario can be useful from several specific tools for specific learning tasks. This situation is not only desirable but also necessary if we want to promote autonomous active learning by means of Personal Learning Environments (PLE) or extrapolate this feature to the new tendency of Massive Open Online Course (MOOC). As the environment scales with the integration of more eLearning tools, we have to face communication and architectural issues. This paper exposes the solution we implemented by means of a centralized access point constituted as an LMS, an architecture based on Tuple Spaces, and the use of eLearning standards to allow communication and information exchange among the different services and components.